Cognitive Skills among Adults: An Impeding Factor for Gender Convergence? - Michele Battisti; Alexandra Fedorets; Lavinia Kinne (Institute of Labor Economics (IZA), 2023)
While gender differences in labor force participation and wages have been studied extensively, gender gaps in cognitive skills among adults are not yet well understood. Using the PIAAC dataset, this paper presents novel findings on cognitive skill distributions by gender across 34 countries. Despite increasing educational equality, inequalities in numeracy skills favoring men compared to women are pervasive. These skill differences account for a sizable part of the gender wage gap. Furthermore, there are larger disadvantages for women at the top of the wage distribution, which are complemented by lower returns to skills compared to men. We also find that these numeracy-wage patterns are especially pronounced for parents and for those with the highest degree in a non-STEM field of study.
Keywords: I24; J16; J24; 330; gender wage gap; skills; numeracy; PIAAC